Integration of social, ecological, political and technological issues into economic development programs: Key to sustainable development of human society - Rajiv K. Sinha; Brijalkumar Soni; Binod Shankar (African Journal of Environmental Economics and Management, 2013)
We need to plan for ‘Development without Destruction’ and manage our environment based on the ethical principle of social equality, economic prosperity with ecological security to achieve the goals of sustainable development. Environmental management and economic development programs should go hand in hand for achieving sustainability in global human society. Changes in the way we develop our economy, eat and drink, live and move, use and discard (as waste) the Earth’s resources, enjoy our lifestyle are needed to be changed quickly to bring us back into balance with our life support systems on Earth. We have also to overcome the ‘greed’ of having more and be ‘contented’ after our ‘needs’ are fulfilled. Greed based society can never be sustainable. The key to growing sustainably is not to produce less but to produce differently, in a way which is environmentally friendly and compatible, that is, by embracing the philosophy of ‘Cleaner Production’; not to consume less but to consume judiciously and efficiently within the regenerative capacity of the Earth ecosystems and with minimum waste generation.